Efficiency Analysis (Debit & Head Losses) of Centrifugal Pumps at PDAM Tirta Terubuk Bengkalis - Wondo Nasrul Hayat; Erwen Martianis (Universitas Medan Area, 2024)
A pump is a device used to raise liquid from a lower position to a higher position. This study analyzes the efficiency of the centrifugal pump used in the air supply system at the Tirta Terukalis Bengkalis Water Supply Company (PDAM). The main focus of the analysis is on the parameters of water discharge, head losses, and centrifugal pump efficiency. This analysis was carried out at PDAM Tirta Terubuk Bengkalis. The data used in this study include the results of an airflow rate of 0.0073 m3/s, a pressure loss of 11 m, and a pump efficiency of 73%. The results of the study revealed that the water discharge was 0.0073 m3/s and the loss stress was 11 m, the pump efficiency reached 73%. This study provides insight into the performance of centrifugal pumps in certain situations in PDAM Bengkalis.